Beyond common analytical limits of radicals detection using the functional SERS substrates; Sensors and Actuators B: Chemical; Vol. 300 - Guselnikova O. A. Olga Andreevna; Postnikov P. S. Pavel Sergeevich; Marque Sylvain R. A.; Svorcik V. Vaclav; Lyutakov O. Oleksy (2019, 2019)
Title screen